Comparative Evaluation of Efficacy of Chemical Versus Surgical Anal Sphincterotomy in patients with Acute Anal Fissure - Junaid Khan Lodhi, Saba Tahir Bokhari, Aasim Malik, Fawad Hameed, Muhammad Zubair, Muhammad Shoaib (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the common causes requiring hospital admission on surgical floor is anal fissure. The quality of life is immensely affected due to painful defecation and bleeding per rectum. Due to poor response to chemical management, acute anal fissure is now treated with surgical methods. Lateral internal sphincterotomy has now become definitive surgical procedure in the treatment of anal fissures. Aim: To compare the efficacy of chemical and surgical lateral internal sphincterotomy in patients of acute anal fissure. Methods: This study was conducted in surgical unit 1 from January 2020 to December 2020. A sample size of 100 were segregated in two groups of 50 each. Group-a was treated withlocal application of glyceryl trinitrate 0.2 percent ointment and group-b was treated with surgical lateral internal sphincterotomy. Results: Patients were ranged between 15-60 years of age. Mean age of the patients was 36.64±10.05 and 33.42±11.47 in group-a and b respectively. In group-a, 13 patients (26%) and in group-b 15 patients (30%) were male and 37 patients (74%) in group-a and 35 patients (70%) were female. Efficacy was observed in 16 patients (32%) of group-a and 50 patients (100%) of group-b. The p value of <0.001 was found to be statistically significant. Conclusion: In conclusion, surgical sphincterotomy was significantly more effective in providing postoperative pain relief (p<0.001). However, chemical sphincterotomy is a non-invasive, cost-effective, easier to apply, well tolerated and effective therapy for anal fissure and is a first line treatment especially in patients who are unwilling or unfit for surgery. Key words: chemical sphincterotomy, lateral internal sphincterotomy, acute anal fissure